Menegosiasikan Kuasa Melalui Rasa: Sejarah Kuliner Sebagai Wujud Resistensi Masyarakat Lokal dalam Bayang Kolonialisme - Leo, Yohanes (Sanata Dharma University, 2025)
Rice has become an inseparable aspect of Indonesians, with a popular opinion that “we haven’t truly eaten, if we haven’t eaten rice.” Accompanied with a spoon and a fork, food, and how we eat have existed within a colonial construct, which doesn’t only appear in the past moment. Colonialism is produced and reproduced in social systems, education, and daily activity. Even so, that term is not merely constructed on the normative values that reduce the community’s resistance to examining the power relationship. “It” is walking simultaneously with a resistance that puts the local knowledge in the mainstream of history—an attempt to negotiate the hegemonic cycles. The barriers between the social context and the praxis are walking “naturally”, making the role of each subject reciprocal. Nevertheless, the domination that appears from the Eurocentric views actually raises the local awareness against the flow in a dignified way. Through local knowledge and collective spirit, processing food becomes a local struggle to reduce the Western hegemony and revitalize the relationship between people and their connection with nature.